A dual-statorwinding induction generator based wind-turbine controlled via super-twisting sliding mode - Talpone, Juan Ignacio (2019)
The dual-stator winding induction generator (DWIG) is a promising electrical machine for wind energy conversion systems, especially in the low/mid power range. Based on previous successful results utilising feed forward control, in this article, a super-twisting (ST) sliding mode improved control set-up is developed to maximise power extraction during low wind regimes. To accomplish this objective, via constant volts/hertz implementation, a ST controller was designed to command the DWIG control winding, such that the tip-speed ratio is robustly maintained at its optimal value. The proposed super-twisting control set-up was experimentally assessed to analyse its performance and to verify its efficiency in an actual generation test bench. The results showed a fast convergence to maximum power operation, avoiding chattering and offsets due to model uncertainties.